Injustiça ambiental: um estudo de caso do bairro do Caju, Zona Portuária do Rio de Janeiro - Ramos, Felipe Pitaro (2014)
Since the end of the monarchic period, and at the birth of the Republic, the social problem of poverty and slums have impact the formation of the city of Rio de Janeiro. Over the years, the question has many faces and many speeches. From the moment in which the Governments of the State and the municipality, since the years of 1950, made the popular representations of the slums part of its political representations, the power of discussion, participation and claim this portion of the population was diminished and dispersed. This fact paved the way for handling investments and public policies that have increased social inequality and, consequently, in places such as the neighborhood of Caju, promoted business growth policies, so intense and predatory who created in concomitance to social problems, severe environmental injustice frames. In search for the strengthening of this stage of debate, this research seeks to collaborate with the portrait of a region barely visible in the municipality of Rio de Janeiro, and that since its occupation as housing area, has been transformed into environmental scanning utility territory, where inequalities arise and imprison an increasing population in the circuits of social and environmental risk. The result is a fragile reality display, and the deeper discussion about the social and environmental situation in the neighborhood of Caju